Strategi Pengembangan Wisata Tuur Ma’asering Di Kelurahan Kumelembuai Kecamatan Tomohon Timur Kota Tomohon - Purba, Theodorus Ucok; Waney, Nordy F.L.; Katiandagho, Theodora M. (AGRI-SOSIOEKONOMI, 2023)
This study aims to formulate a strategy for developing Tuur Ma'asering tourism. This research was carried out from May to August 2022 from preparation to preparation of a research report. The research took place at the Tuur Ma'asering tourist attraction, Tomohon City. The sampling method in this study was Purposive Sampling and Accidental Sampling. The data used were primary data and secondary data. Primary data were obtained from interviews and observation. Secondary data was obtained from the internet. and related agencies in the form of information or data relating to the Tuur Ma'asering tourism development strategy. The analytical method used in this study is SWOT analysis to answer the Tuur Ma'asering tourism development strategy in Tomohon. The results showed that based on the SWOT analysis, the Tuur Ma'asering tourism development strategy is in quadrant 1, meaning that a strategy is needed to support the strengths they have and take advantage of the various opportunities that exist.